Macro-economic determinants of domestic private sector credit in sub-Saharan Africa - Mukuka, Fortune Malama (Graduate School of Business (GSB), 2019)
Credit, to the private sector, is a critical component in driving growth and development the world over. In Africa, the level of credit advanced to the private sector as a percentage of GDP seems to have lagged other more developed regions at 46% of GDP in 2015, in comparison to 120% of global GDP. This study seeks to examine the macro-economic determinants of private sector credit growth in sub-Saharan Africa. The study focuses on independent variables GDP growth (GDP), money supply (M2), inflation (CPI) and interest rates (INTR). Using a panel data approach, twelve sub-Saharan countries are analysed with data observed over a thirty-six-year period, from 1980 to 2015. The size of the panel of countries was determined by the availability of data points on all variables that enabled a balanced panel. Both the random effects and the fixed effects estimation techniques are computed with the random effects method being more significant in the regression analysis, exploring the relationships between the independent variables and the dependent variable. The key findings of the study are that money supply is a significant determinant of private sector credit growth in sub-Saharan Africa showing a positive correlation coefficient. A percentage increase in M2 results in an increase of 0.9% in credit to the private sector. Inflation, on the other hand, dampens the growth in credit to the private sector with a significant negative correlation: a percentage increase results in a reduction of 0.06% in credit to the private sector. GDP growth was statistically insignificant in determining private sector credit growth, with recessionary periods experienced by the sample countries yielding a marginal negative correlation coefficient. Interest rates were also statistically insignificant with a negative correlation to private sector credit showing that credit growth was driven by the underlying need, rather than the cost of credit, in sub-Saharan Africa. It is recommended that policy makers and African governments formulate macro-economic policy that delicately balances the need to drive growth in required money supply, while at the same time maintaining stability in the rate of inflation and related variables. It is also recommended that Financial institutions implement strategies that prioritise mobilisation of loanable funds over interest rate margins. Private sector players are encouraged to focus on promoting investment-led credit consumption in key sectors of the African economy.